Pertanggungjawaban Hukum Penyidik Terhadap Perbuatan Salah Tangkap Dalam Perspektif Hukum Pidana Dan Hak Asasi Manusia - Dedy Irawan; Haris Retno Susmiyati; Orin Gusta Andini (Fakultas Hukum Universitas Mulawarman, 2023)
The wrongful arrest by investigators simultaneously occurs during the arrest process, resulting in a violation of someone's human rights. The responsibility of investigators for wrongful arrests has been regulated in the Criminal Procedure Code and the police professional code of Ethics. The research approach used is a socio-legal approach that aims to find out two main points of discussion. First, the author wants to know and analyze the legal responsibility of investigators who commit wrongful arrests from the perspective of criminal law and human rights. Second, the writer wants to know and analyze the enforcement of criminal responsibility laws against investigators who commit wrongful acts of arrest in the Kutai Kartaneagara Police area. Based on the results of the research, it can be concluded that the responsibility of the investigator is towards the occurrence of wrongful arrests from a criminal law perspective, namely by imposing sanctions on the professional code of ethics of police and disciplinary law or further regulated in Article 13 PP No. 1 of 2003 concerning the Intentions of Members of the National Police of the Republic of Indonesia. Apart from that, from a human rights perspective on wrongful arrests, investigators must be processed following Perkap No. 8 of 2009 concerning the Implementation of Human Rights Principles and Standards in implementing the Duties of the Republic of Indonesia Police. Then the obstacles in enforcing the criminal law against wrongful arrests are caused by the lack of strict application of the police code of ethics sanctions against investigators, specifically regarding sanctions against investigators who violate the police code of ethics.